Online Marketing Strategies in Helping Sales of Processed Chocolate Products and Hampers Vinchoco Surabaya - Evianah Evianah; Dwi Indah Mustikorini; Gimanto Gunawan (Budapest International Research and Critics University, 2022)
The development of the world of technology has changed the habit of interaction in conventional marketing communications into screen to face (internet marketing). With the increase in internet users, this shows that the higher the use of social media which can have an impact on increasing interest in shopping done online, so that it will have an impact on sales.The objectives of this research areto explain online marketing strategies in helping the sale of processed chocolate products and hampers at the online store Vinchco Surabaya.From the results of the SWOT analysis above, it can be concluded that Vinchoco has a strength score of 3.82 which is greater than its weakness score of -3.52. While the score from the analysis of opportunities is 3.38 and the score of analysis of threats is -3.13. This means that Vinchoco is able to survive and survive with the strengths it has and can still get opportunities from this kind of business. The analysis of the threat is much lower than the position of the opportunity. However, Vinchoco must still be able to maintain and improve the factors that become strengths in its business from the internal side. With that strength, hopefully, Vinchoco's vision and mission can continue and the hopes that Vinchoco wants will soon be realized.Suggestions that can be given by the author to the online shop Vinchoco in order to improve its performance and be able to compete in the midst of developing businesses that use digital marketing is to continue to be diligent in promoting their products, providing discounts, maintaining the diversity of product variations, and later being able to open offline stores for consumers. in the city can directly buy at the store and see the product visuals directly.